Novel liquid equilibrium valving on centrifugal microfluidic CD platform - Al-Faqheri, W.; Ibrahim, F.; Thio, T.H.G.; Arof, Hamzah; Madou, M. (2013)
One of the main challenges faced by researchers in the field of microfluidic compact disc (CD) platforms is the control of liquid movement and sequencing during spinning. This paper presents a novel microfluidic valve based on the principle of liquid equilibrium on a rotating CD. The proposed liquid equilibrium valve operates by balancing the pressure produced by the liquids in a source and a venting chamber during spinning. The valve does not require external forces or triggers, and is able to regulate burst frequencies with high accuracy. In this work, we demonstrate that the burst frequency can be significantly raised by making just a small adjustment of the liquid height in the vent chamber. Finally, the proposed valve ng method can be used separately or combined with other valving methods in advance microfluidic processes. Â© 2013 IEEE.